Konsep, Batasan dan Implementasi Penalaran Istislahi dalam Penerapan Hukum Keluarga Islam di Indonesia - Sheyla Nichlatus Sovia; Rendy Dwi Hermanto (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2024)
New issues and phenomena that require legal certainty also develop along with the development of the times and the social context. The Qur'an and Sunnah, which only contain legal issues implicitly, require mujtahids to dig up the law with several methods, one of which is maslahah mursalah or istislah. This research tries to explore matters related to istislahi reasoning, starting from the concept, and limitations, to its implementation in the application of Islamic family law in Indonesia. This research uses a descriptive method with a critical review. The research results show that maslahah mursalah is basically based on preserving the purpose of syariah by taking benefits and rejecting harm (mafsadah). The limitations of this maslahah are: it is not merely conjectural so that it must produce benefits and reject harm (mafsadah), it is general, and it does not conflict with the principal rules of syara'. Thus, the application of the istislahi method in the formation of law is very necessary to face new problems and phenomena that require legal certainty.